An in vivo polymicrobial biofilm wound infection model to study interspecies interactions. - Trevor Dalton (PLoS ONE, 2011)
Chronic wound infections are typically polymicrobial; however, most in vivo studies have focused on monospecies infections. This project was designed to develop an in vivo, polymicrobial, biofilm-related, infected wound model in order to study multispecies biofilm dynamics and in relation to wound chronicity. Multispecies biofilms consisting of both Gram negative and Gram positive strains, as well as aerobes and anaerobes, were grown in vitro and then transplanted onto the wounds of mice. These in vitro-to-in vivo multi-species biofilm transplants generated polymicrobial wound infections, which remained heterogeneous with four bacterial species throughout the experiment. We observed that wounded mice given multispecies biofilm infections displayed a wound healing impairment over mice infected with a single-species of bacteria. In addition, the bacteria in the polymicrobial wound infections displayed increased antimicrobial tolerance in comparison to those in single species infections. These data suggest that synergistic interactions between different bacterial species in wounds may contribute to healing delays and/or antibiotic tolerance.